Determining the relative importance of quality factors for crowdfunding platforms - Allah Pitchay, Anwar; Mohd Thas Thaker, Mohamed Asmy; Mohd Thas Thaker, Hassanudin; Amin, Md. Fouad Bin (Creative Decisions Foundation, 2019)
A crowdfunding platform provides a facility for anyone with internet access to transmit an idea to a social network with the goal of gathering funding for their works or projects. A quality crowdfunding platform acts as an indicator of the donors’ ability to provide funds to the projects. In the existing literature on the quality factors of crowdfunding platforms, no systematic approach has been applied to prioritize these quality factors. The task of identifying the quality factors of a crowdfunding platform has been absent in the existing literature. The aim of this study is to use the Analytic Hierarchy Process (AHP) to identify and rank the relative weights of the quality factors of crowdfunding platforms. The results show that ‘functionality’ emerged as the most crucial criterion. The research findings also provide insightful information to crowdfunding platform providers so that they may improve the effectiveness and efficiency of their platforms.